The Impact of the COVID-19 Pandemic on Pregnancy Planning Behaviors - Angela C. Flynn; Kimberley Kavanagh; Andrea D. Smith; Lucilla Poston; Sara L. White (Women's Health Reports, 2021)
Background: Our understanding of how the coronavirus disease 2019 (COVID-19) pandemic has impacted decision-making for women planning to conceive is unclear. We aimed to investigate how the COVID-19 pandemic has influenced pregnancy planning behaviors. Methods: An online questionnaire of closed- and open-ended questions was utilized to capture pregnancy planning behaviors and reported behavioral changes during the COVID-19 pandemic in women planning pregnancy between January and July 2020. Closed-ended questions were analyzed quantitatively, and thematic framework analysis was utilized for open-ended responses. Results: A total of 504 questionnaires were included for analysis. The majority of respondents lived in the United Kingdom. Ninety-two percent of the women were still planning a pregnancy but over half (n?=?267) reported that COVID-19 had affected their plans, with 72% of these (n?=?189) deliberately postponing pregnancy. Concerns were predominantly over changes in antenatal care, but also fear of adverse effects of the virus on mother and baby. From the thematic analysis (n?=?37), lack of services to remove contraceptive devices and provide fertility treatment were also cited. In contrast, 27% (n?=?71) reported bringing their pregnancy plans forward; common themes included recalibration of priorities and cancelled or changed plans. Conclusions: The COVID-19 pandemic influenced pregnancy-planning behaviors with many women reporting postponement of pregnancy. These alterations in behavior could impact the health and wellbeing of women planning pregnancy while having important implications for health care services worldwide. Continued provision of family planning and fertility services should be ensured to mitigate the effect of future outbreaks or pandemics.